2010
DOI: 10.1007/s10519-010-9412-7
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic Effects of DCDC2 and DYX1C1 Genes on Language and Mathematics Traits in Nuclear Families of Developmental Dyslexia

Abstract: Converging evidence indicates that developmental problems in oral language and mathematics can predate or co-occur with developmental dyslexia (DD). Substantial genetic correlations have been found between language, mathematics and reading traits, independent of the method of sampling. We tested for association of variants of two DD susceptibility genes, DCDC2 and DYX1C1, in nuclear families ascertained through a proband with DD using concurrent measurements of language and mathematics in both probands and sib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 48 publications
1
29
0
2
Order By: Relevance
“…Phenotypic and genotypic data were available for 804 offspring belonging to 493 unrelated Italian nuclear families of probands with DD, all of which have already participated in our previous association studies on these candidate genes (Marino et al 2003(Marino et al , 2004(Marino et al , 2005(Marino et al , 2007(Marino et al , 2011(Marino et al , 2012Mascheretti et al 2014a, b). Reading was available for 612 offspring, spelling for 579 offspring, memory letters for 355 offspring and memory digits for 480 offspring.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Phenotypic and genotypic data were available for 804 offspring belonging to 493 unrelated Italian nuclear families of probands with DD, all of which have already participated in our previous association studies on these candidate genes (Marino et al 2003(Marino et al , 2004(Marino et al , 2005(Marino et al , 2007(Marino et al , 2011(Marino et al , 2012Mascheretti et al 2014a, b). Reading was available for 612 offspring, spelling for 579 offspring, memory letters for 355 offspring and memory digits for 480 offspring.…”
Section: Resultsmentioning
confidence: 99%
“…This study is based on an ongoing project on the genetic basis of DD (Marino et al 2003(Marino et al , 2004(Marino et al , 2005(Marino et al , 2007(Marino et al , 2011(Marino et al , 2012Mascheretti et al 2014a, b). The ascertainment scheme has been reported in detail elsewhere (Marino et al 2003).…”
Section: Samplementioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have suggested that comprehension involves the automatic and unconscious simulation of past experiences, relying on the processing of sensorimotor representations (see for instance Bergen et al, 2007;Marino et al 2011). According to this "simulation hypothesis", when we understand the meaning of an action-related verb, we unconsciously and automatically simulate the experience of the action described by the verb (Bergen et al, 2007;Barsalou, 1999 Tettamanti et al (2005) observed in a fMRI study the activation during the processing of action-related sentences of the cortical circuit responsible for the planning and execution of the same actions (observationexecution matching system, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to nonrandom ascertainment, under random ascertainment, all families including those with no affected member are recruited with probability of unity. It is fundamental to this article that non-random ascertainment has important effects on the structure of an ascertained subpopulation [15][16][17]. Obviously, it introduces classical ascertainment bias [9,10,18].…”
Section: Introductionmentioning
confidence: 99%